(untitled) (Vietnam Journal of Community Medicine, 2024)
Objectives: Evaluation of surgical results of patients with anomalous pulmonary venous return at Hanoi Heart Hospital. Subjects and methods: The study described 65 cases of anomalous pulmonary venous return with indications for surgery at Hanoi Heart Hospital from 2016 to 2021. Results: Early surgical outcomes for anomalous pulmonary venous return were good, with an overall mortality rate of 1.54% and this is a patient with obstruction and emergency surgery. The rate of complications after surgery is 4.62%, including: 1.54% pleural effusion; 1.54% of premature left atrial stenosis required re-operation and 1.54% of pleural effusion with pericardial effusion. The median duration of mechanical ventilation was 72.0 ± 66.53 hours; the average duration of postoperative resuscitation was 5.74 ± 3.90 days. Conclusion: Relatively good surgical results, low premature mortality rate; surgical techniques used depend on the type of disease. Studies with large sample sizes and multicenters are needed to comprehensively evaluate treatment results.